2017
DOI: 10.17507/tpls.0711.19
|View full text |Cite
|
Sign up to set email alerts
|

Construct Under-representation and Construct Irrelevant Variances on IELTS Academic Writing Task 1: Is There Any Threat to Validity?

Abstract: Abstract-The study reports on the validity of IELTS Academic Writing Task One (IAWTO) and compares and assesses the performance descriptors, i.e., coherence and cohesion, lexical resource and grammatical range, employed on IAWTO and IELTS Academic Writing Task Two (IAWTT). To these objectives, the data used were 53 participants' responses to graphic prompts driven by IELTS scoring rubrics, descriptive prompt, and retrospective, rather than concurrent, think-aloud protocols for detecting the cognitive validity … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 35 publications
(27 reference statements)
0
5
0
Order By: Relevance
“…The relationship between the input and the response in this type of task is broader and more direct compared to Task 1 in the general version, as test takers are expected to base their response entirely on the input. Alavi and Masjedlou (2017) found that test takers and instructors perceive the first writing task in the academic version to be intelligence-based and to require more time for thinking than for writing. Students' underperformance on this cognitively demanding task can emotionally affect their performance on the following task (Alavi and Masjedlou, 2017).…”
Section: Writingmentioning
confidence: 99%
See 1 more Smart Citation
“…The relationship between the input and the response in this type of task is broader and more direct compared to Task 1 in the general version, as test takers are expected to base their response entirely on the input. Alavi and Masjedlou (2017) found that test takers and instructors perceive the first writing task in the academic version to be intelligence-based and to require more time for thinking than for writing. Students' underperformance on this cognitively demanding task can emotionally affect their performance on the following task (Alavi and Masjedlou, 2017).…”
Section: Writingmentioning
confidence: 99%
“…Alavi and Masjedlou (2017) found that test takers and instructors perceive the first writing task in the academic version to be intelligence-based and to require more time for thinking than for writing. Students' underperformance on this cognitively demanding task can emotionally affect their performance on the following task (Alavi and Masjedlou, 2017). Compared to Task 2, the critique of Task 1 is reversedwe have a higher level of authenticity (i.e., it is highly plausible that real-life academic tasks would involve more thinking than writing) and a lower level of validity (e.g., diagram reading is construct-irrelevant for assessment of writing skills).…”
Section: Writingmentioning
confidence: 99%
“…A number of studies, for example, have focused on task difficulty, showing that test-takers may score differently depending on the task type. For instance, Alavi and Masjedlou (2017) found that the difficulty of Task 1 was not consistent for test-takers (see also Hamid, et al, 2019). They found that diagram analysis was more difficult for Iranian test-takers than the interpretation of bar charts.…”
Section: Literature Reviewmentioning
confidence: 99%
“…With 45 Iranian participants, Ahmadi, Riasati, and Bavali conducted a study to evaluate test takers' performance in IELTS academic writing, focusing on the table and bar chart format of Task 1 (Ahmadi et al, 2019). In a study more closely related to the feedback concerns of the present research, Alavi, Nemati, and Dorri Kafrani investigated the more problematic features of IELTS academic writing Task 2, emphasizing the need for corrective feedback and support (Alavi et al, 2020). Their results indicated that effective training, feedback, and practice were key to achieving better results.…”
Section: Introductionmentioning
confidence: 96%